2007
DOI: 10.1680/adcr.2007.19.3.93
|View full text |Cite
|
Sign up to set email alerts
|

Influence of P(V) on the characteristics of calcium silicates and the hydration of clinkers

Abstract: The effect of the addition of small amounts of meat and bone meal (MBM) ash on the clinkering process and on the hydraulic reactivity of obtained clinkers was studied. The study was aimed at simulating the clinker burning process in an industrial furnace that replaced up to 20 wt% conventional fuel with MBM used as alternative fuel. Laboratory clinkers were obtained by adding from 0 . 07 to 0 . 88 wt.% of MBM ash to an industrial raw mixture, and were compared with a clinker obtained without additions. The fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
1
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 11 publications
2
19
1
2
Order By: Relevance
“…Therefore, there must be other phenomena as well, along with above mentioned reason, which cause the 138% increase in free lime content at 7 t/hr MBM feeding. It has been shown [7], [23]- [27] that a high level of phosphorous stabilizes belite and hence inhibits the reaction between CaO and belite to form alite. Due to this reason the free lime content can be increased.…”
Section: Mbm Feed Rate(t/hr)mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, there must be other phenomena as well, along with above mentioned reason, which cause the 138% increase in free lime content at 7 t/hr MBM feeding. It has been shown [7], [23]- [27] that a high level of phosphorous stabilizes belite and hence inhibits the reaction between CaO and belite to form alite. Due to this reason the free lime content can be increased.…”
Section: Mbm Feed Rate(t/hr)mentioning
confidence: 99%
“…However, one study has been carried out to find out the effect of MBM ash addition on the clinkering process and hydraulic reactivity of clinker [7]. In another study [8] the air demand and energy input in the rotary kiln burner were investigated through an ASPEN PLUS model by partly replacing primary fuel by MBM.…”
Section: Introductionmentioning
confidence: 99%
“…Phosphorus has been shown to negatively influence the formation of alite and increases the amount of belite and CaO(s) formed. With increasing amounts of phosphorus pentoxide in the raw material of clinker, phosphorus was shown to primarily enter the belite phase and to a lesser extent the alite phase (Gutt, 1963;Nastac et al, 2007;Stanek and Sulovsky, 2009). At concentrations above 1% phosphorus pentoxide, a solid solution of phosphorus and belite forms (Nurse, 1952).…”
Section: Theoretical Calculationsmentioning
confidence: 99%
“…The use of wastederived fuels from agricultural crops, animal meat or bone meal, for example, leads to increased phosphorus content in cement. It has been shown that phosphorus decomposes or inhibits the formation of alite while stabilising belite and generating free lime (Halicz et al, 1984;Nastac et al, 2007;Nurse, 1952;Stanek and Sulovsky, 2009). The amount of alite in cement is of great importance because it is the most important contributor to the development of strength in concrete in the first 28 d. Because phosphorus is expected to increase when traditional fossil fuels are replaced with alternative biomass-based fuels, both theoretical and practical studies on how an increased phosphorous content influences clinker minerals have been performed.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, the flow of exhaust gases and the effect on operational parameters were found [8]. Furthermore, the effect of MBM ash addition on the clinkering process, a review of energy volarisation of MBM as well as environmental impacts of using MBM in cement kilns have been investigated [9]- [11].…”
Section: Introductionmentioning
confidence: 99%